Laser mirror structure, manufacturing method thereof and laser processing device

By setting piezoelectric ceramics and copper layers in the laser mirror structure, the dynamic swing of the laser beam is achieved, and the problem of uneven energy distribution in laser processing of extra-thick sheets is solved, the cutting and welding quality is improved, and the laser process window is expanded.

CN119902346APending Publication Date: 2025-04-29MAXPHOTONICS CORP +2

Patent Information

Application Number
CN202510283562.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

It is difficult for fixed-focus high-power laser processing equipment to achieve both laser processing efficiency and quality during the cutting and welding of extra-thick sheets. It is mainly due to the uneven energy distribution of fixed spots during heat transfer, resulting in cutting or welding defects, and the process window is narrow.

Method used

By providing a piezoelectric ceramic, a first intermediate bonding layer, a copper layer and a second intermediate bonding layer in the laser mirror structure, an electric field is applied to the piezoelectric ceramic by using the copper layer to swing the laser beam, so that the laser focus will dynamically swing in the thickness direction of the processing target, thereby alleviating the problem of temperature unevenness.

Benefits of technology

The quality of the cutting surface and welding joints of extra-thick plates is effectively improved, and the laser process window for laser efficient cutting and welding of extra-thick plates is significantly expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119902346A_ABST
    Figure CN119902346A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of laser processing. The invention provides a laser reflector structure, a manufacturing method thereof and a laser processing device. The laser reflector structure comprises a reflector main body, the reflector main body comprises piezoelectric ceramic, and a first intermediate bonding layer, a copper layer, a second intermediate bonding layer and reflecting glass which are laminated on the first surface of the piezoelectric ceramic. According to the invention, by arranging the first intermediate bonding layer, the copper layer and the second intermediate bonding layer, connection between the piezoelectric ceramic and the reflecting glass is realized, and by applying an electric field to the piezoelectric ceramic through the copper layer, swinging of a collimated laser beam in the laser can be realized, so that the collimated laser beam can pass through subsequent elements such as a focus lens and the like; dynamic swing of the laser focus in the thickness direction of a machining target is achieved, the problem that the temperature between the upper plate face and the lower plate face is not uniform in the ultra-thick plate cutting operation and welding operation process is effectively solved, the cutting face quality and the internal quality of a welding joint can be improved, and a laser process window during efficient laser cutting and ultra-thick plate welding is remarkably enlarged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of laser technology and relates to a laser reflector structure and a manufacturing method thereof and a laser processing device. Background Art

[0002] Laser processing equipment, with its high precision, high speed and non-contact characteristics, has gradually replaced traditional mechanical processing methods and become an indispensable part of modern manufacturing. It has gradually become a more common material cutting and welding process equipment in many fields such as automobile manufacturing, aerospace, and shipbuilding.

[0003] In order to achieve the cutting and welding of metal materials, especially extra-thick metal plate materials (hereinafter referred to as: extra-thick plates), laser processing equipment is developing towards integration and high power. At present, the output power of laser benchmark products has reached 220kW. However, for extra-thick plates, it is difficult for high-power laser processing equipment with fixed focus to achieve both laser processing efficiency and laser processing quality. The main limitation is that when the fixed spot transfers heat to the extra-thick plate, the energy distribution of the extra-thick plate along the thickness direction is uneven. Whether the positive defocus setting (the laser spot focus is above the surface of the workpiece to be processed) or the negative defocus setting (the laser spot focus is below the surface of the workpiece to be processed) is adopted, it is difficult to ensure the uniformity of heat transfer on the cutting processing surface or welding processing surface of the extra-thick plate, resulting in cutting or welding defects to varying degrees during the processing of the extra-thick plate. Moreover, for extra-thick plates, due to the uneven energy distribution during the fixed focus laser processing, the process window is very narrow. Any slight parameter adjustment may lead to processing quality problems, increase the difficulty of process debugging, and reduce operating efficiency.

[0004] CN1607059A discloses a laser bidirectional cutting method, which is achieved by placing the workpiece between two laser heads with opposite laser beam emission directions and in a straight line. With this method, two low-power laser generators can be used to replace a high-power laser generator to cut a plate of a certain thickness, thereby greatly reducing the cost of laser cutting equipment. Similarly, CN2661357Y discloses a dual-laser head laser cutting machine, which uses two low-power laser heads to simultaneously and synchronously cut the plate in both directions, thereby replacing a high-power laser cutting machine that cuts a plate of a certain thickness in one direction, greatly reducing the manufacturing and use costs of laser cutting equipment. However, the above-mentioned multi-point focusing will face the problem of cutting accuracy, and still cannot completely solve the problem of uneven energy distribution in the thickness direction, and the system complexity increases, and the maintenance cost is high.

[0005] Therefore, there is still a need to research and develop relevant technologies for laser processing in order to solve the problem of laser processing of extra-thick plates in a simple and effective way. Summary of the invention

[0006] In view of the problems existing in the prior art, the purpose of the present invention is to provide a laser reflector structure and a manufacturing method thereof and a laser processing device, wherein the laser reflector structure includes a reflector body; the reflector body includes a piezoelectric ceramic, and a first intermediate bonding layer, a copper layer, a second intermediate bonding layer and a reflective glass are stacked on its first surface. The present invention realizes the connection between the piezoelectric ceramic and the reflective glass by setting the first intermediate bonding layer, the copper layer and the second intermediate bonding layer, and applies an electric field to the piezoelectric ceramic through the copper layer, so that the collimated laser beam in the laser can be swung, so that it can realize the dynamic swing of the laser focus in the thickness direction of the processing target through subsequent focusing mirrors and other components, which will effectively alleviate the problem of uneven temperature between the upper and lower plate surfaces during the cutting and welding of extra-thick plates, improve the quality of the cutting surface and the internal quality of the welding joint, and significantly expand the laser process window for efficient laser cutting and welding of extra-thick plates.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a laser reflector structure, comprising a reflector body; the reflector body comprises a piezoelectric ceramic, the piezoelectric ceramic having a first surface and a second surface opposite to each other; a first intermediate bonding layer, a copper layer, a second intermediate bonding layer and a reflective glass are stacked on the first surface; the second intermediate bonding layer comprises an oxygen-philic metal layer; a first electrical connection point is arranged on the second surface, and a second electrical connection point is arranged on the copper layer, for applying an external electric field to the piezoelectric ceramic.

[0009] In order to realize the swing of the collimated laser beam in the laser, and subsequently realize the dynamic swing of the laser focus in the thickness direction of the processing target, the concept of the present invention is to combine piezoelectric ceramics with reflective glass, and realize the change of the position of the reflective glass by applying an external electric field to the piezoelectric ceramics, thereby controlling the swing of the collimated laser beam in the laser. Piezoelectric ceramics have piezoelectric effect and inverse piezoelectric effect, which can achieve the mutual conversion of mechanical energy and electrical energy. They are ideal materials for piezoelectric drive devices, have the characteristics of fast response speed and voltage regulation drive, and are widely used in electronics, drive, medical and other fields. The displacement and thrust output by the voltage-driven piezoelectric ceramics are proportional to the applied voltage. Therefore, the piezoelectric ceramics are connected to the optical reflective glass, and the optical reflective glass is driven by the piezoelectric ceramic displacement to cause the same frequency displacement, which will achieve the swing effect after the parallel beam is reflected. However, there are two main problems to be solved to achieve the effective combination of piezoelectric ceramics and reflective glass and ensure that they can play a role continuously and stably. In particular, due to the limitation of the Curie temperature of piezoelectric ceramics, there is a technical bottleneck in the direct low-temperature connection of piezoelectric ceramics and glass.

[0010] To solve the above problems, the present invention sets a copper layer between the piezoelectric ceramic and the reflective glass as an intermediate layer connecting the two, and the copper layer can play a conductive role to achieve voltage application on one side of the piezoelectric ceramic. In order to achieve the combination of the reflective glass and the copper layer, the present invention sets the second intermediate bonding layer to promote bonding with the copper layer, effectively improving the bonding strength between the reflective glass and the copper layer.

[0011] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0012] As a preferred technical solution of the present invention, the composition of the piezoelectric ceramic includes at least one of lead zirconate titanate, barium titanate or lead magnesium niobate.

[0013] Preferably, the piezoelectric ceramic is doped with hafnium oxide (HfO2), and the doping amount of hafnium oxide is ≤1wt%, for example, 1wt%, 0.8wt%, 0.6wt%, 0.4wt%, 0.2wt%, 0.1wt% or 0.05wt%, etc.

[0014] In the present invention, the appropriate addition of HfO2 to the piezoelectric ceramic can increase the Curie temperature of the piezoelectric ceramic, which is beneficial to expand the process window for welding (brazing) the piezoelectric ceramic and the copper film at low temperature. When the addition amount is greater than 1wt%, the Curie temperature is further increased to exceed 210°C, but d 33 The value drops below 680pm / V, which deteriorates the piezoelectric functionality.

[0015] The present invention 33 The value is an important parameter to measure the piezoelectric properties of materials. Specifically, it is a type of piezoelectric strain constant, which indicates the proportional relationship between the strain generated in the direction of the applied electric field (usually a unit electric field strength is applied in the polarization direction, i.e. the 3-axis direction) and the electric field strength in that direction. Simply put, when an electric field is applied in a specific direction of a piezoelectric material (usually the direction after polarization), the degree of elongation or shortening of the material in this direction is the amount of electrostriction (strain) generated. Higher d 33 A higher value means that the material can produce a larger deformation under the same electric field.

[0016] Preferably, the Curie temperature of the piezoelectric ceramic is 180-210° C., for example, 180° C., 185° C., 190° C., 195° C., 200° C., 205° C. or 210° C. 33 The value is 680-700pm / V, for example, 680pm / V, 685pm / V, 690pm / V, 695pm / V or 700pm / V.

[0017] Preferably, a first coating is provided on the first surface of the piezoelectric ceramic, and the first intermediate bonding layer is provided on the surface of the first coating away from the piezoelectric ceramic; a second coating is provided on the second surface of the piezoelectric ceramic, and the first electrical connection point is provided on the second coating.

[0018] Preferably, the materials of the first coating and the second coating are independently selected from at least one of Ni, Ag, Au, Cu, Ti or Pt; the thicknesses of the first coating and the second coating are independently selected from 3 to 10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, etc.

[0019] In the present invention, the first plating layer is provided to improve the weldability of the piezoelectric ceramic, to improve the Curie temperature of the piezoelectric ceramic, to expand the welding process window between the piezoelectric ceramic and the copper layer, and to enable the piezoelectric ceramic to be better welded and combined with the copper layer.

[0020] As a preferred technical solution of the present invention, the first intermediate bonding layer includes a brazing layer.

[0021] Preferably, based on the mass of the brazing layer as 100%, the brazing layer includes (52-y)% In, (48-z)% Sn and (x+y)% Ga, and x=0-2, for example, 0, 0.3, 0.5, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 2, etc.; y=0-2, for example, 0, 0.3, 0.5, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 2, etc.; the welding formation temperature of the brazing layer is 40-50°C lower than the Curie temperature of the piezoelectric ceramic, for example, 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, etc.

[0022] Preferably, the thickness of the soldering layer is 0.02-0.05 mm, such as 0.02 mm, 0.03 mm, 0.04 mm or 0.05 mm, etc., and the tensile strength of the soldering interface between the soldering layer and the copper layer is greater than 6 MPa.

[0023] As a preferred technical solution of the present invention, the purity of copper in the copper layer is 99.9% to 100%; the thickness of the copper layer is ≥0.05mm, for example, 0.05mm, 0.06mm, 0.08mm, 0.1mm, 0.12mm, 0.15mm, 0.18mm, 0.2mm, 0.25mm, 0.3mm, 0.35mm or 0.4mm; the thermal conductivity of the copper layer is ≥390W / (m·K).

[0024] Preferably, the copper layer has an uncovered heat dissipation portion, and the area of ​​the heat dissipation portion is ≥ 250 mm 2 , for example 250mm 2、280mm 2 、300mm 2 、330mm 2 、350mm 2 、380mm 2 , 400mm 2 、420mm 2 , 450mm 2 、480mm 2 or 500mm 2 The uncovered portion refers to a portion that is not covered by the first intermediate bonding layer, the second intermediate bonding layer, and the housing described below, and upper and lower opposite side surfaces of the portion are exposed to the environment.

[0025] In the laser reflector structure, although the reflective glass has a high reflectivity and a very low refractive index, after long-term irradiation with high-power laser, heat can still be transferred to the brazing layer through the oxygen-philic metal layer and the copper layer with high thermal conductivity. Since the melting point of the brazing layer is low, it is easily affected. In particular, in the present invention, if the thickness of the copper layer is less than 0.05mm and the heat dissipation area is less than 250mm 2 The copper film tends to increase the temperature of the reflective glass sheet to more than 50°C during service. Usually, the temperature of 50°C to 60°C softens the brazing layer, thereby significantly reducing the strength of the interface between the piezoelectric ceramic, the copper layer and the first intermediate bonding layer. The service life of the laser reflector structure under 10kW laser irradiation is less than 240h. Therefore, in the present invention, the copper layer is designed to accelerate the heat dissipation effect of the laser reflector element, thereby improving the stability and service life of the structure.

[0026] Preferably, the oxygen-affinity metal layer comprises an aluminum layer; the purity of aluminum in the aluminum layer is 99.8% to 100%; the thickness of the oxygen-affinity metal layer is 0.01 to 0.02 mm, for example, 0.01 mm, 0.011 mm, 0.012 mm, 0.013 mm, 0.014 mm, 0.015 mm, 0.016 mm, 0.017 mm, 0.018 mm, 0.019 mm or 0.02 mm, etc.

[0027] In the present invention, an aluminum layer is preferably used as the second intermediate bonding layer. The aluminum element can diffuse to the interface with the glass body and react with the non-bridging oxygen atoms in the glass body at the interface to achieve connection. At the same time, the aluminum element also diffuses into the copper layer to achieve diffusion connection between copper and aluminum, thereby effectively improving the bonding strength and achieving reliable connection between the copper layer and the glass body.

[0028] Preferably, the reflective glass comprises a glass body, and a reflective film arranged on a surface of the glass body on a side away from the second intermediate bonding layer, and the reflectivity of the reflective film is ≥ 99.7%, such as 99.7%, 99.8% or 99.9%.

[0029] Preferably, based on the mass of the glass body as 100%, the glass body comprises 90% to 94% SiO2, 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5% or 94%, etc., 3% to 5% K2O, for example, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8% or 5%, etc.; and 3% to 5% Na2O, for example, 3%, 3.3%, 3.5%, 3.8%, 4%, 4.3%, 4.5%, 4.8% or 5%, etc.; and the reflectivity of the glass body is 88% to 92%, for example, 88%, 88.5%, 89%, 89.5%, 90%, 90.5%, 91%, 91.5% or 92%, etc.

[0030] In the present invention, the glass body should have appropriate K2O and Na2O contents. Lower K2O and Na2O contents are not conducive to the bonding connection between the glass body and the copper layer. Higher K2O and Na2O contents can reduce the reflectivity of the glass body, increase the temperature of the copper film under 10kW laser irradiation, and thus affect the service life of the reflector element. Therefore, by designing the composition of the glass body and providing a reflective film, it is possible to achieve high reflectivity while avoiding the weakening of the bonding strength between the copper layer, the second intermediate bonding layer and the reflective glass in the pressed body under high temperature environment.

[0031] As a preferred technical solution of the present invention, the laser reflector structure also includes an upper shell and a lower shell; the upper shell and the lower shell are connected by insulating glue to form an outer shell; the reflector body is arranged in the outer shell, the reflective glass faces the upper shell, and the piezoelectric ceramic faces the lower shell; the upper shell is provided with a first optical path hole and a second optical path hole for the incidence and reflection of the laser.

[0032] Preferably, the copper layer extends to a region where the upper shell and the lower shell are connected, and is fixed by the insulating glue.

[0033] Preferably, the lower shell is provided with a through hole, the reflector body is arranged above the through hole, so that part of the second surface of the piezoelectric ceramic is exposed in the through hole, and the rest of the second surface is fixed to the lower shell by insulating glue.

[0034] In a second aspect, the present invention provides a method for manufacturing the laser reflector structure according to the first aspect, the manufacturing method comprising the following steps:

[0035] Providing reflective glass, oxygen-affinity metal layer diaphragm, copper layer diaphragm, first intermediate bonding layer raw materials and piezoelectric ceramics;

[0036] The oxygen-philic metal layer film and the copper layer film are sequentially stacked on one side surface of the reflective glass to obtain a laminated body; the laminated body is pressed, and the oxygen-philic metal layer film forms an oxygen-philic metal layer as a second intermediate bonding layer to obtain a pressed body;

[0037] The piezoelectric ceramic has a first surface and a second surface opposite to each other; the first intermediate bonding layer raw material is used to form a first intermediate bonding layer between one side of the copper layer diaphragm in the obtained pressed body and the first surface of the piezoelectric ceramic, and the copper layer diaphragm forms a copper layer to constitute a reflector body, thereby obtaining a laser reflector structure;

[0038] A first electrical connection point is arranged on the second surface of the piezoelectric ceramic, and a second electrical connection point is arranged on the copper layer, for applying an external electric field to the piezoelectric ceramic.

[0039] As a preferred technical solution of the present invention, the manufacturing method includes: cleaning the reflective glass, the oxygen-philic metal layer membrane and the copper layer membrane in advance to remove surface oil stains. The cleaning includes cleaning with acetone and alcohol and drying.

[0040] In the present invention, the copper layer diaphragm and the piezoelectric ceramic are connected by a brazing process, which can greatly improve the conductivity between the copper layer and the piezoelectric ceramic. The metal connection formed by brazing is stronger than the conventional glue connection, which can improve the problem of weakening the piezoelectric effect of the piezoelectric ceramic due to the flexibility of the glue, and ensure that the piezoelectric ceramic fully exerts its piezoelectric effect under the action of the electric field.

[0041] Preferably, the pressing is carried out at a vacuum degree of 10 -5 ~10 -2 Pa vacuum environment, for example, 10 -5 Pa, 10 -4 Pa, 10 -3 Pa or 10 -2 Pa et al.

[0042] Preferably, the pressing pressure is 30-50 MPa, for example, 30 MPa, 33 MPa, 35 MPa, 38 MPa, 40 MPa, 42 MPa, 44 MPa, 46 MPa, 48 MPa or 50 MPa.

[0043] Preferably, at the beginning of pressing, the temperature is raised to 350-450°C, for example, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C or 450°C, at a rate of 30-50°C / min, for example, 30°C / min, 35°C / min, 40°C / min, 45°C / min or 50°C / min, and the temperature is kept at 3-5min, for example, 3min, 3.5min, 4min, 4.5min or 5min, etc.

[0044] Preferably, during the heat preservation and pressure preservation process, a DC voltage of 300-400V, such as 300V, 320V, 340V, 360V, 380V or 400V, is applied through the copper layer diaphragm.

[0045] In the present invention, the pressing is preferably carried out under the synergistic effect of temperature, pressure and electric field. These external fields can strengthen the breaking of the chemical bonds of the alkali metal oxides in the glass body, promote the migration of oxygen atoms to the interface between the glass body and the second intermediate bonding layer (such as the aluminum layer), and the elements in the second intermediate bonding layer, such as aluminum elements, also diffuse to the bonding interface with the glass body at the same time, so that the aluminum ions and the non-bridging oxygen atoms in the glass body undergo oxidation reaction at the interface to achieve connection. At the same time, the mutual diffusion rate of copper and aluminum is accelerated under the action of the electric field, thereby achieving the bonding connection between the glass body and the aluminum layer and the diffusion connection between the copper layer and the aluminum layer at the same time.

[0046] If the second intermediate bonding layer is not used, and the glass body is bonded directly through the copper layer. Under the same process conditions, the bonding strength between the glass body and the copper layer is less than 2MPa. This is because copper's affinity for oxygen is weaker than that of oxygen-affinity metals, such as aluminum. For example, when the pressure is lower than 30MPa and the temperature is lower than 350°C, the overall interface bonding strength of the pressed body will be reduced. To achieve the same level of bonding strength, a higher external field effect of temperature-pressure-electric field needs to be applied. However, when the temperature exceeds 450°C and the pressure exceeds 50MPa, the glass body will undergo microscopic compression deformation, and the reflective film on its surface will also be damaged.

[0047] In the present invention, heat preservation and pressure holding in the pressing process are more critical. If the heat preservation and pressure holding time is too low, the mutual diffusion of elements under the electric field is insufficient, which affects the overall interface bonding strength; if the heat preservation time is too long, although the reaction mutual diffusion of the interface under the electric field is sufficient, the width of the reaction diffusion interface is significantly increased, and obvious and complex intermetallic compounds IMs are easily formed in the interface. These IMs are often brittle phases. Although they are beneficial to improving the strength to a certain extent, they are detrimental to the fatigue life of the component during service. Similarly, the control and effect of the DC voltage are similar to the heat preservation time. The greater the voltage, the easier it is to promote interdiffusion at the interface, and it is also easier to form IMs at the interface. The reduction in voltage is not conducive to the improvement of the overall interface bonding strength. In short, the degree of application of the three external fields of temperature-pressure-electric field should be reasonably adjusted according to the actual situation to greatly improve the bonding strength and increase the service life of the component.

[0048] Preferably, after the heat preservation and pressure preservation is completed, the pressed body is cooled to below 60°C at a cooling rate of 5 to 10°C / min, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, and taken out to obtain the pressed body.

[0049] As a preferred technical solution of the present invention, the manufacturing method includes cleaning the piezoelectric ceramic and the copper layer of the pressed body in advance to remove surface oil stains. The cleaning includes cleaning with acetone or alcohol and drying.

[0050] Preferably, the first intermediate joining layer raw material includes brazing material.

[0051] Preferably, based on the mass of the solder being 100%, the solder comprises (52-y)% In, (48-z)% Sn and (x+y)% Ga, and x=0-2, for example, 0, 0.3, 0.5, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 2, etc.; y=0-2, for example, 0, 0.3, 0.5, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 2, etc.

[0052] In the present invention, by adjusting the components in the solder, its melting point and welding temperature range can be controlled. The preferred melting point is 108-118°C, and the welding temperature range is 118-130°C. It should be noted that the present invention ignores the IMs formed at the soldering interface, and the components and proportions in the formed solder layer are the same as those in the solder.

[0053] Preferably, the brazing material comprises a pre-alloyed brazing sheet having a thickness of 0.02 to 0.05 mm, for example, 0.02 mm, 0.025 mm, 0.03 mm, 0.035 mm, 0.04 mm, 0.045 mm or 0.05 mm.

[0054] In the present invention, the thickness of the pre-alloyed brazing sheet is less than 0.02 mm. Under the brazing pressure, the brazing material is easily squeezed out, reducing the bonding strength of the brazing interface. If the thickness is greater than 0.05 mm, a large number of IMs may exist at the brazing interface, which also affects the fatigue life of the laser reflector element.

[0055] Preferably, flux is provided on the surface of the pre-alloyed brazing sheet, and the thickness of the flux is 3 to 5 μm, for example, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm or 5 μm.

[0056] In the present invention, if the thickness of the flux pre-coated on the surface is less than 3 μm, the wettability of the soldering interface tends to be insufficient and the soldering strength is reduced; if the thickness is greater than 5 μm, more flux tends to remain on the edge of the piezoelectric ceramic and Cu after soldering, affecting the surface quality of the laser reflector element welding.

[0057] Preferably, the area value of the pre-alloyed brazing sheet is calculated based on the theoretical area to be brazed, and its area value = theoretical area to be brazed × (0.94-0.95), to ensure that after vacuum low-temperature brazing, the actual brazing area reaches more than 99% of the theoretical area to be brazed.

[0058] Preferably, based on 100% by mass of the soldering flux, the soldering flux comprises 35% to 55% of rosin (C 19 H 29 COOH), for example, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52% or 55%; 5% to 20% of a halogenated compound activator, for example, 5%, 8%, 10%, 12%, 15%, 18% or 20%; and 25% to 35% of ethylene oxide ((C2H4O) n , n represents the number of repeating units in the ethylene oxide chain), for example, it can be 25%, 28%, 30%, 32% or 35%, etc., and the remainder is additives and organic solvents.

[0059] Preferably, the halogen-containing compound activator includes stannous chloride (SnCl2); the additive includes succinic acid and / or malic acid; and the organic solvent includes at least one of ethanol, acetone or acetate.

[0060] Preferably, the method of forming the first intermediate bonding layer includes brazing.

[0061] Preferably, the brazing is performed at a vacuum degree of 10 -4 -10 -2 Pa vacuum environment, for example 10 -4 Pa, 10 -3Pa or 10 -2 Pa et al.

[0062] Preferably, the brazing pressure is 0.03-0.04 N / mm 2 , for example 0.03N / mm 2 , 0.032N / mm 2 、0.034N / mm 2 , 0.036N / mm 2 、0.038N / mm 2 or 0.04N / mm 2 wait.

[0063] In the present invention, if the brazing pressure is too low, the bonding strength of the brazing interface tends to be insufficient; if the brazing pressure is too high, the molten brazing material at the target temperature of 118-130°C is easily squeezed out, which not only affects the brazing surface quality, but may also form a cold weld due to the lack of brazing material in some parts, and is also likely to affect the bonding strength of the brazing interface.

[0064] Preferably, the brazing temperature is 40-50°C lower than the Curie temperature of the piezoelectric ceramic to avoid damaging the d 33 Values, such as 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, etc.

[0065] Preferably, the brazing temperature is 118-130°C, for example, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C.

[0066] Preferably, the brazing process includes heating to 90°C at a heating rate of 10-12°C / min, such as 10°C / min, 11°C / min or 12°C / min, and then heating to 100-118°C at a heating rate of 8-10°C / min, such as 8°C / min, 9°C / min or 10°C / min, and then heating to 110°C, 112°C, 114°C, 116°C or 118°C at a heating rate of 3-5°C / min, such as 3°C / min, The temperature is raised to 118-130°C, such as 118°C, 120°C, 122°C, 124°C, 126°C, 128°C or 130°C, etc., and kept warm for 90-100s, such as 90s, 92s, 94s, 96s, 98s or 100s, etc., at a cooling rate of 3-5°C / min, such as 3°C / min, 4°C / min or 5°C / min, etc., and then cooled to below 40°C with the furnace, and taken out to obtain the reflector body.

[0067] In the present invention, after the temperature rises to the target temperature (brazing temperature) of 118-130°C, if the holding time is less than 90s, the pore discharge time in the brazing interface tends to be insufficient, the interface porosity is high, and the interface fatigue life after brazing is affected; if the holding time is higher than 100s, too much Cu-Al IMs are easily formed at the brazing interface, and the brazing interface becomes significantly widened, which also affects the interface fatigue life after brazing.

[0068] In the present invention, the brazing process is a vacuum low-temperature brazing process, which presents a gradual heating + gradual cooling form as a whole, which can reduce the temperature overshoot in the heating process, and can also reduce the increase of interface residual stress caused by rapid cooling of the brazing interface in the cooling process, thereby ensuring the service fatigue life of the brazing interface.

[0069] In short, by vacuum brazing the copper layer diaphragm and the piezoelectric ceramic, the brazing process adopts the form of gradual heating + gradual cooling to control the temperature, pressure, insulation time and other parameters in the brazing process. At the same time, matching the pre-alloyed brazing sheet with specific chemical composition and thickness can achieve high-quality welding, improve the bonding strength of the brazing interface, and extend the service life of the component brazing interface.

[0070] As a preferred technical solution of the present invention, the manufacturing method further comprises:

[0071] An upper shell, a lower shell and insulating glue are provided; the upper shell, the lower shell and the reflector body are assembled using the insulating glue to obtain the laser reflector structure.

[0072] It should be noted that the copper layer membrane should have a geometric center feature so that the formed copper layer has sufficient contact area to combine with other layer structures, and can be extended to obtain a suitable heat dissipation part and a part connected and fixed to the shell, but its specific shape is not limited.

[0073] In a third aspect, the present invention provides a laser processing device, wherein the laser processing device comprises the laser reflector structure described in the first aspect.

[0074] It should be noted that the present invention does not list all point values ​​within the above numerical range one by one, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0075] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0076] In the laser reflector structure provided by the present invention, a first intermediate bonding layer, a copper layer and a second intermediate bonding layer are arranged to realize a stable connection between the piezoelectric ceramic and the reflective glass. By applying an electric field to the piezoelectric ceramic through the copper layer, the collimated laser beam in the laser can be swung, so that the laser focus can be dynamically swung in the thickness direction of the processing target through subsequent focusing mirrors and other components. This will effectively alleviate the problem of uneven temperature between the upper and lower plate surfaces during the cutting and welding operations of extra-thick plates, improve the quality of the cutting surface and the internal quality of the welding joint, and significantly expand the laser process window for efficient laser cutting and welding of extra-thick plates.

[0077] The manufacturing method of the present invention first presses the reflective glass, the oxygen-philic metal layer diaphragm and the copper layer diaphragm to obtain a pressed body, and then brazes the pressed body with the piezoelectric ceramic. By optimizing and controlling the pressing process and the brazing process, the bonding strength between the layers in the laser reflector structure can be improved, effectively extending the service life of the laser reflector structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] Figure 1 It is a schematic diagram of a working state of the laser reflection mirror structure of Example 1.

[0079] Figure 2 It is a schematic diagram of another working state of the laser reflection mirror structure of Example 1.

[0080] Figure 3 It is a schematic diagram of another working state of the laser reflection mirror structure of Example 1.

[0081] In the figure: 1-shell, 2-first intermediate bonding layer, 3-piezoelectric ceramic, 4-copper layer, 5-reflective glass, 6-AC power supply, 7-collimated light beam, 8-steel plate thickness section, 9-second intermediate bonding layer, 10-insulating glue, 11-upper shell, 12-lower shell, 13-first optical path hole, 14-second optical path hole. DETAILED DESCRIPTION

[0082] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0083] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0084] Example 1

[0085] The present embodiment provides a laser reflector structure, which includes a reflector body; the reflector body includes a piezoelectric ceramic 3, and the piezoelectric ceramic 3 has a first surface and a second surface opposite to each other; a first intermediate bonding layer 2, a copper layer 4, a second intermediate bonding layer 9 and a reflecting glass 5 are stacked on the first surface; the first intermediate bonding layer 2 includes a soldering layer, and the second intermediate bonding layer 9 includes an oxygen-philic metal layer; a first electrical connection point is provided on the second surface, and a second electrical connection point is provided on the copper layer 4, which is used to apply an external electric field to the piezoelectric ceramic 3.

[0086] The piezoelectric ceramic 3 is composed of lead zirconate titanate and doped with 0.6 wt % of hafnium oxide, so that the Curie temperature of the piezoelectric ceramic 3 is 194° C. 33 The value is 692pm / V; a first coating is provided on the first surface of the piezoelectric ceramic 3, and the first intermediate bonding layer is provided on the surface of the first coating away from the piezoelectric ceramic 3; a second coating is provided on the second surface of the piezoelectric ceramic 3, and the first electrical connection point is provided on the second coating; the materials of the first coating and the second coating are both Ag layers, and the thickness is 5μm.

[0087] Taking the mass of the brazing layer as 100%, the brazing layer includes 51% In, 47% Sn and 2% Ga, and the welding forming temperature of the brazing layer is lower than the Curie temperature of the piezoelectric ceramic 3 to 42° C.; the thickness of the brazing layer is 0.036 mm;

[0088] The purity of copper in the copper layer 4 is 99.99%; the thickness of the copper layer 4 is 0.08 mm; the thermal conductivity of the copper layer 4 is 398 W / (m·K); the copper layer 4 has an uncovered heat dissipation portion, and the area of ​​the heat dissipation portion is 338 mm 2 .

[0089] The oxygen-affinity metal layer is an aluminum layer; the purity of aluminum in the aluminum layer is 99.9%; and the thickness of the oxygen-affinity metal layer is 0.015 mm.

[0090] The reflective glass 5 includes a glass body and a reflective film arranged on the surface of the glass body on one side away from the second intermediate bonding layer 9; based on the mass of the glass body being 100%, the glass body includes 92% SiO2, 4% K2O and 4% Na2O; the reflectivity of the glass body is 91%; and the reflectivity of the reflective film is ≥99.7%.

[0091] The laser reflector structure also includes an upper shell 11 and a lower shell 12; the upper shell 11 and the lower shell 12 are connected by an insulating glue 10 to form a shell 1; the reflector body is arranged in the shell 1, the reflecting glass 5 faces the upper shell 11, and the piezoelectric ceramic 3 faces the lower shell 12; the upper shell 11 is provided with a first optical path hole 13 and a second optical path hole 14 for the incidence and reflection of the laser; the copper layer 4 extends to the area where the upper shell 11 and the lower shell 12 are connected, and is fixed by the insulating glue 10; the lower shell 12 is provided with a through hole, and the reflector body is arranged above the through hole, so that part of the second surface of the piezoelectric ceramic 3 is exposed in the through hole, and the remaining part of the second surface is fixed to the lower shell 12 by the insulating glue 10.

[0092] This embodiment also provides a method for manufacturing the laser reflector structure, including:

[0093] (1) Provide a reflective glass 5, an oxygen-philic metal layer diaphragm, a copper layer diaphragm, a solder and a piezoelectric ceramic 3; the solder is a pre-alloyed solder sheet with a thickness of 0.036 mm; a solder flux is provided on the surface of the pre-alloyed solder sheet, and the thickness of the solder flux is 4 μm; based on the mass of the solder flux being 100%, the solder flux comprises 45% of rosin, 12% of halogenated compound activator stannous chloride, and 30% of ethylene oxide, and the remainder is an additive succinic acid and organic solvents ethanol and acetone.

[0094] (2) The reflective glass 5, the oxygen-philic metal layer membrane and the copper layer membrane are cleaned in advance, and the cleaning includes cleaning with acetone and alcohol and drying to remove surface oil stains; the oxygen-philic metal layer membrane and the copper layer membrane are sequentially stacked on one side surface of the reflective glass 5 to obtain a laminate; the laminate is pressed, and the pressing is carried out at a vacuum degree of 2×10 -5 Pa, the pressing applied pressure is 38MPa, at the beginning of pressing, the temperature is raised to 400°C at a rate of 40°C / min, and the temperature is kept and pressed for 4 minutes; during the temperature-keeping and pressure-keeping process, a DC voltage of 350V is applied through the copper layer diaphragm; the temperature-keeping and pressure-keeping allows the oxygen-philic metal layer diaphragm to form an oxygen-philic metal layer as the second intermediate bonding layer 9. After the temperature-keeping and pressure-keeping is completed, it is cooled to below 60°C at a cooling rate of 10°C / min, and the pressed body is taken out.

[0095] (3) The piezoelectric ceramic 3 has a first surface and a second surface opposite to each other; the copper layer diaphragm in the obtained pressed body is brazed to the first surface of the piezoelectric ceramic 3 by using the brazing material, and the brazing is performed under a vacuum degree of 8×10 -4 The brazing pressure is 0.032N / mm2 ; The brazing temperature is 149°C, which is 45°C lower than the Curie temperature of the piezoelectric ceramic 3; specifically, the brazing process includes heating to 90°C at a heating rate of 11°C / min, then heating to 101°C at a heating rate of 8°C / min, and then heating to the brazing temperature of 123°C at a heating rate of 4°C / min. After keeping warm for 95s, the brazing material forms a brazing layer as the first intermediate bonding layer 2, and the copper layer diaphragm forms a copper layer 4 to constitute the reflector body, and then cools to 100°C at a cooling rate of 4°C / min, and then cools to below 40°C in the furnace to obtain the reflector body.

[0096] (4) Provide an upper shell 11, a lower shell 12 and an insulating glue 10; use the insulating glue 10 to assemble the upper shell 11, the lower shell 12 and the reflector body, so that a first electrical connection point is set on the second surface of the piezoelectric ceramic 3, and a second electrical connection point is set on the copper layer 4, so as to apply an external electric field to the piezoelectric ceramic to obtain the laser reflector structure.

[0097] Example 2

[0098] This embodiment provides a laser reflector structure, in which the hafnium oxide doping amount of the piezoelectric ceramic 3 in the laser reflector structure is adjusted from 0.6 wt % to 1.3 wt %. Except for the above, other conditions are exactly the same as those in Embodiment 1.

[0099] Example 3

[0100] This embodiment provides a laser reflector structure, in which the thickness of the copper layer 4 (copper layer membrane) in the laser reflector structure is adjusted from 0.08 mm to 0.02 mm, and the area of ​​the heat dissipation part of the copper layer 4 is adjusted from 338 mm to 1.3 mm. 2 Adjusted to 200mm 2 Except for the above, other conditions are exactly the same as those in Example 1.

[0101] Example 4

[0102] This embodiment provides a laser reflector structure, in which the proportion of SiO2 in the glass body of the laser reflector structure is adjusted from 92% to 96%, the proportion of K2O is adjusted from 4% to 1.8%, and the proportion of Na2O is adjusted from 4% to 2%. Except for the above, other conditions are exactly the same as those in Example 1.

[0103] Example 5

[0104] This embodiment provides a laser reflector structure. In step (2) of the manufacturing method of the laser reflector structure, the pressure applied during pressing is adjusted from 38MPa to 53Mpa, and the temperature is adjusted from 400°C to 340°C. Except for the above, other conditions are exactly the same as those in Example 1.

[0105] Example 6

[0106] This embodiment provides a laser reflector structure. In step (2) of the manufacturing method of the laser reflector structure, the pressure applied during pressing is adjusted from 38 MPa to 28 MPa, and the temperature is adjusted from 400°C to 480°C. Except for the above, other conditions are exactly the same as those in Example 1.

[0107] Example 7

[0108] This embodiment provides a laser reflector structure. In the step (2) of the manufacturing method of the laser reflector structure, the heat preservation and pressure holding time of the pressing is adjusted from 4 minutes to 2 minutes. Except for the above, other conditions are exactly the same as those in Example 1.

[0109] Example 8

[0110] This embodiment provides a laser reflector structure, and the heat preservation and pressure holding time of pressing in step (2) of the manufacturing method of the laser reflector structure is adjusted from 4 minutes to 6 minutes. Except for the above, other conditions are exactly the same as those in Example 1.

[0111] Example 9

[0112] This embodiment provides a laser reflector structure, and the thickness of the brazing layer (braze pre-alloyed brazing sheet) of the laser reflector structure is adjusted from 0.036 mm to 0.015 mm. Except for the above, other conditions are exactly the same as those in Embodiment 1.

[0113] Example 10

[0114] This embodiment provides a laser reflector structure, and the thickness of the brazing layer (braze pre-alloyed brazing sheet) of the laser reflector structure is adjusted from 0.036 mm to 0.055 mm. Except for the above, other conditions are exactly the same as those in Embodiment 1.

[0115] Embodiment 11

[0116] This embodiment provides a laser reflector structure, wherein the brazing pressure in step (3) of the manufacturing method of the laser reflector structure is changed from 0.032 N / mm 2 Adjusted to 0.018N / mm 2 Except for the above, other conditions are exactly the same as those in Example 1.

[0117] Example 12

[0118] This embodiment provides a laser reflector structure, wherein the brazing pressure in step (3) of the manufacturing method of the laser reflector structure is changed from 0.032 N / mm 2 Adjusted to 0.055N / mm 2 Except for the above, other conditions are exactly the same as those in Example 1.

[0119] Example 13

[0120] This embodiment provides a laser reflector structure, and in step (3) of the manufacturing method of the laser reflector structure, the brazing holding time is adjusted from 95s to 80s. Except for the above, other conditions are exactly the same as those in Example 1.

[0121] Embodiment 14

[0122] This embodiment provides a laser reflector structure, and in step (3) of the manufacturing method of the laser reflector structure, the brazing holding time is adjusted from 95s to 110s. Except for the above, other conditions are exactly the same as those in Example 1.

[0123] Comparative Example 1

[0124] This comparative example provides a laser reflector structure, which does not contain a second intermediate bonding layer 9, that is, in step (2) of the manufacturing method of the laser reflector structure, only reflective glass 5 and copper layer membrane are used for pressing to obtain a pressed body. Except for the above, other conditions are exactly the same as those in Example 1.

[0125] Comparative Example 2

[0126] This comparative example provides a laser reflector structure, in which the first intermediate bonding layer 2 in the laser reflector structure is replaced by a conductive glue layer instead of a soldering layer, that is, in step (3) of the manufacturing method of the laser reflector structure, a conductive glue is used to bond the piezoelectric ceramic 3 to one side of the copper layer diaphragm in the pressed body. Except for the above, other conditions are exactly the same as those in Example 1.

[0127] Comparing Example 1 with Comparative Example 1, the laser reflector structure obtained in Example 1 forms a fixation and connection between the piezoelectric ceramic and the reflective glass through the first intermediate bonding layer, the copper layer and the second intermediate bonding layer, and the bonding strength is higher and stronger, which can effectively improve the problem of weakening the piezoelectric effect of the piezoelectric ceramic due to the flexibility of the glue, and ensure that the piezoelectric ceramic can fully exert its piezoelectric effect under the action of the electric field.

[0128] Comparing Example 1 with Example 2, the proper addition of HfO2 to the piezoelectric ceramic in Example 1 can increase the Curie temperature of the piezoelectric ceramic, which is beneficial to expand the process window for welding (brazing) the piezoelectric ceramic and the copper film at low temperature. However, when the addition amount in Example 2 is greater than 1wt%, the Curie temperature is further increased to exceed 210℃, but the 33 The value drops below 680pm / V, which deteriorates the piezoelectric functionality.

[0129] Comparing Example 1 with Example 3, the thickness of the copper layer and the area of ​​the heat dissipation part in Example 1 are appropriate, and the heat dissipation performance is excellent. The thickness of the copper layer in Example 3 is less than 0.05 mm and the heat dissipation area is less than 250 mm 2 At this time, the copper film tends to cause the temperature of the reflective glass sheet to rise to above 50°C during service, causing the solder layer to soften, thereby significantly reducing the strength of the interface between the piezoelectric ceramic, the first intermediate bonding layer and the copper layer. The service life of the laser reflector structure under 10kW laser power irradiation is less than 240h.

[0130] Comparing Example 1 with Example 4, the contents of K2O and Na2O in Example 1 are appropriate, which can achieve high reflectivity and ensure the connection strength between the glass body and the copper layer. However, the lower contents of K2O and Na2O in Example 4 are not conducive to the bonding connection between the glass body and the copper layer. However, higher contents of K2O and Na2O can reduce the reflectivity of the glass body, which will increase the temperature of the copper film under 10kW laser irradiation, thereby affecting the service life of the reflector element. Therefore, it is necessary to reasonably design and control the composition of the glass body. On this basis, by setting a reflective film in Example 1, the reflective glass as a whole can achieve high reflectivity while improving the bonding strength between the copper layer in the pressed body, the second intermediate bonding layer and the reflective glass.

[0131] Comparing Comparative Example 2 with Example 1, if the second intermediate bonding layer is not used and the copper layer is directly bonded to the glass body, under the same process conditions, the bonding strength between the glass body and the copper layer is less than 2 MPa. This is because copper has a weaker affinity for oxygen than oxygen-affinity metal aluminum.

[0132] Comparing Example 5 and Example 6 with Example 1, when the oxygen-philic metal layer is used as the second intermediate connection layer, the pressure of the pressing process for forming it is lower than 30MPa and the temperature is lower than 350°C, which will reduce the overall interface bonding strength of the pressed body. When the temperature exceeds 450°C and the pressure exceeds 50MPa, the glass body will undergo microscopic compression deformation and the reflective film on its surface will also be damaged.

[0133] Compared with Example 1, when making the pressed body, the heat preservation and pressure holding time of Example 7 and Example 8 is too short, that is, when it is less than 3 minutes, the mutual diffusion of elements under the electric field is insufficient, affecting the overall interface bonding strength of Cu-Al-glass; when the heat preservation time is too long, that is, when it is more than 5 minutes, although the reaction mutual diffusion of the Cu-Al interface under the electric field is sufficient, the width of the reaction diffusion interface is significantly increased, and obvious complex intermetallic compounds IMs are easily formed in the interface. These IMs are often brittle phases, which are easy to improve the strength, but are not conducive to improving the fatigue life of the components during service.

[0134] Comparing Example 9 and Example 10 with Example 1, the thickness of the pre-alloyed brazing sheet used in the present invention is less than 0.02 mm. Under the action of brazing pressure, the brazing material is easily squeezed out, reducing the bonding strength of the brazing interface. When the thickness is greater than 0.05 mm, a large number of IMs may exist at the brazing interface, which also affects the service fatigue life of the laser reflector element.

[0135] Compared with Example 1, the welding pressure of Example 11 and Example 12 during brazing was too low, less than 0.03 N / mm 2 The brazing interface bonding strength is insufficient; the brazing pressure is too large, higher than 0.04N / mm 2 When the solder is molten, it will be squeezed out at the target soldering temperature, which will not only affect the surface quality of the soldering, but also form a cold solder joint due to the lack of solder in some parts, and also affect the bonding strength of the soldering interface.

[0136] Compared with Example 1, when brazing, after the temperature rises to the brazing temperature, if the holding time is less than 90 s, the pore time in the brazing interface tends to be insufficient, and the interface porosity is high, which affects the service fatigue life of the interface after brazing. If the holding time is higher than 100 s, too much Cu-Al IMs are easily formed at the brazing interface, and the brazing interface becomes significantly widened, which also affects the service fatigue life of the interface after brazing.

[0137] The laser reflector structure and manufacturing method obtained in Example 1 are the best among the above-mentioned embodiments and comparative examples. When the laser reflector structure obtained in Example 1 is used to reflect laser light in a laser processing device, an external electric field is applied to the piezoelectric ceramic 3, and the charge distribution inside the piezoelectric ceramic 3 changes, thereby generating tension or pressure on the internal electrode. This tension or pressure will cause the piezoelectric ceramic 3 to deform slightly, that is, it will generate mechanical displacement under the action of force, thereby driving the reflective glass 5 to achieve precisely controllable micro-movement. By changing the slight displacement of the reflective glass 5, the up and down fluctuation position of the focus of the focused light beam can be dynamically adjusted. Specifically, if Figure 1 , Figure 2 and Figure 3As shown in the working schematic diagram, the first electrical connection point and the second electrical connection point in the laser reflector structure are electrically connected to the external AC power supply 6, and an external electric field is applied to the piezoelectric ceramic 3 to control the piezoelectric ceramic 3 to produce a piezoelectric effect and deform, so that the reflective glass 5 is displaced; at this time, the collimated laser beam 7 is incident on the reflective glass 5 from the first optical path hole 13 of the upper shell 11, and after being reflected by it, it is emitted through the second optical path hole 14 of the upper shell 11 to reach the steel plate to be processed; due to the displacement of the reflective glass 5, the focus of the laser swings in the thickness direction of the steel plate thickness section, for example, from position ① to ② and then back to ①, and then from position ① to ③ and then back to ①, and so on and so forth, so as to realize laser processing of extra thick steel plates.

[0138] To summarize, the laser reflector structure provided by the present invention is provided with a first intermediate bonding layer, a copper layer and a second intermediate bonding layer, so as to realize a stable connection between the piezoelectric ceramic and the reflective glass. By applying an electric field to the piezoelectric ceramic through the copper layer, the collimated laser beam in the laser can be swung, so that the laser focus can be dynamically swung in the thickness direction of the processing target through subsequent focusing mirrors and other components. This will effectively alleviate the problem of uneven temperature between the upper and lower plate surfaces during the cutting and welding operations of extra-thick plates, improve the quality of the cutting surface and the internal quality of the welding joint, and significantly expand the laser process window for efficient laser cutting and welding of extra-thick plates.

[0139] The manufacturing method of the present invention first presses the reflective glass, the oxygen-philic metal layer diaphragm and the copper layer diaphragm to obtain a pressed body, and then brazes the pressed body with the piezoelectric ceramic. By optimizing and controlling the pressing process and the brazing process, the bonding strength between the layers in the laser reflector structure can be improved, effectively extending the service life of the laser reflector structure.

[0140] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0141] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0142] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A laser reflector structure, characterized in that: The invention comprises a reflector body; the reflector body comprises a piezoelectric ceramic, the piezoelectric ceramic has a first surface and a second surface opposite to each other; a first intermediate bonding layer, a copper layer, a second intermediate bonding layer and a reflective glass are stacked on the first surface; the second intermediate bonding layer comprises an oxygen-philic metal layer; a first electrical connection point is arranged on the second surface, and a second electrical connection point is arranged on the copper layer, for applying an external electric field to the piezoelectric ceramic.

2. The laser reflection mirror structure according to claim 1, characterized in that: The piezoelectric ceramic comprises at least one of lead zirconate titanate, barium titanate or lead magnesium niobate; And / or, the piezoelectric ceramic is doped with hafnium oxide, and the doping amount of hafnium oxide is ≤1wt%; And / or, the Curie temperature of the piezoelectric ceramic is 180-210°C, d 33 The value is 680~700pm / V; And / or, a first coating is provided on the first surface of the piezoelectric ceramic, and the first intermediate bonding layer is provided on a surface of the first coating away from the piezoelectric ceramic; a second coating is provided on the second surface of the piezoelectric ceramic, and the first electrical connection point is provided on the second coating; And / or, the materials of the first plating layer and the second plating layer are independently selected from at least one of Ni, Ag, Au, Cu, Ti or Pt; the thicknesses of the first plating layer and the second plating layer are independently selected from 3 to 10 μm.

3. The laser reflection mirror structure according to claim 1 or 2, characterized in that: The first intermediate bonding layer comprises a brazing layer; And / or, based on the mass of the brazing layer being 100%, the brazing layer comprises (52-y)% of In, (48-z)% of Sn and (x+y)% of Ga, and x=0-2, y=0-2; the welding formation temperature of the brazing layer is 40-50° C. lower than the Curie temperature of the piezoelectric ceramic; And / or, the thickness of the soldering layer is 0.02-0.05 mm; and the tensile strength of the soldering interface between the soldering layer and the copper layer is greater than 6 MPa.

4. The laser reflector structure according to any one of claims 1 to 3, characterized in that: The purity of copper in the copper layer is 99.9% to 100%; the thickness of the copper layer is ≥ 0.05 mm; the copper layer has an uncovered heat dissipation portion, and the area of ​​the heat dissipation portion is ≥ 250 mm 2 ; And / or, the oxygen-affinity metal layer comprises an aluminum layer; the purity of aluminum in the aluminum layer is 99.8% to 100%; the thickness of the oxygen-affinity metal layer is 0.01 to 0.02 mm; And / or, the reflective glass comprises a glass body, and a reflective film provided on a surface of the glass body on a side away from the second intermediate bonding layer; the reflectivity of the reflective film is ≥99.7%; And / or, based on the mass of the glass body being 100%, the glass body comprises 90% to 94% of SiO2, 3% to 5% of K2O and 3% to 5% of Na2O; and the reflectivity of the glass body is 88% to 92%.

5. The laser reflector structure according to any one of claims 1 to 4, characterized in that: The laser reflector structure further includes an upper shell and a lower shell; the upper shell and the lower shell are connected by insulating glue to form a shell; the reflector body is arranged in the shell, the reflective glass faces the upper shell, and the piezoelectric ceramic faces the lower shell; the upper shell is provided with a first optical path hole and a second optical path hole for the incidence and reflection of the laser; And / or, the copper layer extends to a region where the upper shell and the lower shell are connected, and is fixed by the insulating glue; And / or, the lower shell is provided with a through hole, the reflector body is arranged above the through hole, so that part of the second surface of the piezoelectric ceramic is exposed in the through hole, and the rest of the second surface is fixed to the lower shell by insulating glue.

6. A method for manufacturing a laser reflector structure, characterized in that: The manufacturing method comprises the following steps: Providing reflective glass, oxygen-affinity metal layer diaphragm, copper layer diaphragm, first intermediate bonding layer raw materials and piezoelectric ceramics; The oxygen-philic metal layer film and the copper layer film are sequentially stacked on one side surface of the reflective glass to obtain a laminated body; the laminated body is pressed, and the oxygen-philic metal layer film forms an oxygen-philic metal layer as a second intermediate bonding layer to obtain a pressed body; The piezoelectric ceramic has a first surface and a second surface opposite to each other; the first intermediate bonding layer raw material is used to form a first intermediate bonding layer between one side of the copper layer diaphragm in the obtained pressed body and the first surface of the piezoelectric ceramic, and the copper layer diaphragm forms a copper layer to constitute a reflector body, thereby obtaining a laser reflector structure; A first electrical connection point is arranged on the second surface of the piezoelectric ceramic, and a second electrical connection point is arranged on the copper layer, for applying an external electric field to the piezoelectric ceramic.

7. The method for manufacturing a laser reflector structure according to claim 6, characterized in that: The manufacturing method includes: cleaning the reflective glass, the oxygen-affinity metal layer membrane and the copper layer membrane in advance to remove surface oil stains; And / or, the pressing is carried out at a vacuum degree of 10 -5 ~10 -2 Pa in a vacuum environment; And / or, the pressing pressure is 30-50 MPa; and / or, at the beginning of pressing, heating to 350-450° C. at a rate of 30-50° C. / min, and maintaining the temperature and pressure for 3-5 min; and / or, during the heat and pressure keeping process, applying a DC voltage of 300 to 400 V through the copper layer diaphragm; And / or, after the heat preservation and pressure preservation are completed, the pressed body is cooled to below 60° C. at a temperature reduction rate of 5 to 10° C. / min and taken out to obtain the pressed body.

8. The method for manufacturing a laser reflector structure according to claim 6 or 7, characterized in that: The first intermediate bonding layer raw material includes a brazing material, and the brazing material includes a pre-alloyed brazing sheet with a thickness of 0.02 to 0.05 mm; And / or, a soldering flux is provided on the surface of the pre-alloyed brazing sheet, and the thickness of the soldering flux is 3 to 5 μm; And / or, based on the mass of the soldering flux being 100%, the soldering flux comprises 35% to 55% of rosin, 5% to 20% of a halogenated compound activator, and 25% to 35% of ethylene oxide, with the remainder being additives and organic solvents; And / or, the halogen-containing compound activator includes stannous chloride; the additive includes succinic acid and / or malic acid; the organic solvent includes at least one of ethanol, acetone or acetate; and / or, the method of forming the first intermediate bonding layer comprises brazing; And / or, the brazing is carried out at a vacuum degree of 10 -4 ~10 -2 Pa vacuum environment; And / or, the brazing pressure is 0.03-0.04 N / mm 2 ; and / or, the brazing temperature is 40-50° C. lower than the Curie temperature of the piezoelectric ceramic; And / or, the brazing temperature is 118-130°C; And / or, the brazing process includes heating the temperature to 90°C at a heating rate of 10-12°C / min, then heating the temperature to 100-118°C at a heating rate of 8-10°C / min, then heating the temperature to 118-130°C at a heating rate of 3-5°C / min, keeping the temperature for 90-100s, cooling the temperature to 100°C at a cooling rate of 3-5°C / min, and then cooling the temperature to below 40°C in the furnace to obtain the reflector body.

9. The method for manufacturing a laser reflector structure according to any one of claims 6 to 8, characterized in that: The manufacturing method further comprises: An upper shell, a lower shell and insulating glue are provided; the upper shell, the lower shell and the reflector body are assembled using the insulating glue to obtain the laser reflector structure.

10. A laser processing device, characterized in that: A laser reflector structure comprising any one of claims 1 to 5.

Citation Information

Patent Citations

  • Laser bi-directional cutting method

    CN1607059A

Cited By

  • Electric field composite glass and metal continuous selective laser welding method

    CN121798153A